Understanding the diagnosis of catheter-related bloodstream infection: real-time monitoring of biofilm growth dynamics using time-lapse optical microscopy - Díaz-Navarro, Marta; Samaniego, Rafael; Piqueras, Juan Carlos; Díez, Rafael; Hafian, Rama; Manzano, Irene; Muñoz, Patricia; Guembe, María (Frontiers in Cellular and Infection Microbiology, 2023)
Background. The differential time to positivity (DTTP) technique is recommended for the conservative diagnosis of catheter-related bloodstream infection (C-RBSI). The technique is based on a 120-minute difference between microbial growth in blood drawn through the catheter and blood drawn through a peripheral vein. However, this cut-off has failed to confirm C-RBSI caused by Candida spp. and Staphylococcus aureus.Objective. We hypothesized that the biofilm of both microorganisms disperses faster than that of other microorganisms and that microbial load is rapidly equalised between catheter and peripheral blood. Therefore, our aim was to compare the biofilm dynamics of various microorganisms.Methods. Biofilm of ATCC strains of methicillin-resistant Staphylococcus epidermidis, methicillin-susceptible S. aureus, Enterococcus faecalis, Escherichia coli and Candida albicans was grown on silicon disks and analyzed using time-lapse optical microscopy. The time-lapse images of biofilms were processed using ImageJ2 software. Cell dispersal time and biofilm thickness were calculated.Results. The mean (standard deviation) dispersal time in C. albicans and S. aureus biofilms was at least nearly 3 hours lower than in biofilm of S. epidermidis, and at least 15 minutes than in E. faecalis and E. coli biofilms.Our findings could explain why early dissemination of cells in C. albicans and S. aureus prevents us from confirming or ruling out the catheter as the source of the bloodstream infection using the cut-off of 120 minutes in the DTTP technique. In addition, DTTP may not be sufficiently reliable for E. coli since their dispersion time is less than the cutoff of 120 minutes.